2014
DOI: 10.5785/30-1-570
|View full text |Cite
|
Sign up to set email alerts
|

The write approach: Can R2L help at tertiary level?

Abstract: This article discusses a one-year intervention that was implemented using the Read to Learn (R2L) approach with 46 isiZulu-speaking students at a South African University in 2011. All the students were in the BCom4 Access Programme at the University of KwaZulu-Natal and originated from Quintile 1-4 schools. Participating students were taught to understand and read selected texts. They were then assisted through a process of 'scaffolding', in which they ultimately learnt how to independently write a text of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Students with low levels of vocabulary associated with the language of instruction and with the discourse struggle with anaphoric resolution. 12,13 Moreover, when second-language students do not have opportunities to practise anaphoric resolution, there is an impact on the depth of understanding that they are likely to access and thus the time that it takes for them to form a deep understanding of lecture content. 13 Two international studies have reported that South African learners are ranked amongst the lowest in international standards in reading, and that the language in which learners were taught at school and the language of assessment most likely contributes to the students' poor academic performance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Students with low levels of vocabulary associated with the language of instruction and with the discourse struggle with anaphoric resolution. 12,13 Moreover, when second-language students do not have opportunities to practise anaphoric resolution, there is an impact on the depth of understanding that they are likely to access and thus the time that it takes for them to form a deep understanding of lecture content. 13 Two international studies have reported that South African learners are ranked amongst the lowest in international standards in reading, and that the language in which learners were taught at school and the language of assessment most likely contributes to the students' poor academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Moreover, when second-language students do not have opportunities to practise anaphoric resolution, there is an impact on the depth of understanding that they are likely to access and thus the time that it takes for them to form a deep understanding of lecture content. 13 Two international studies have reported that South African learners are ranked amongst the lowest in international standards in reading, and that the language in which learners were taught at school and the language of assessment most likely contributes to the students' poor academic performance. 28,29 As students progress through school, it is essential that they learn to formulate a cohesive representation of their texts 8 ; thus the focus should lie in the development of language proficiency 3,6,7,30 and reading ability [5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations